Наука управног права и наука о управи као популарне науке у Мађарској - Rixer, Ádám (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abstract: Why should the science of public administration not also be one of the popular sciences? Why only physicists have the privilege to talk about their own field in a way that is accessible, understandable and interesting for many? After defining the general concept of science promotion, this study briefly presents the main goals of promotion, including the skills that can be developed the most through these promotion efforts, the administrative areas that, in our opinion, are of the most public interest, new communication opportunities and channels and concrete (methodological) solutions that increase opportunities for addressing and dialogue, including the interdisciplinary fields that use and present results of administrative law. It proceeds to consider answers regarding the matters of what skills and knowledge the ideal promoter should have and what social target groups can potentially be the focus of promotion efforts. The study also captures the general and administrative knowledge limitations of science promotion before concluding with a summary of the results obtained.